Quantitative Evaluation of Toxic Polyglycine Biosynthesis and Aggregation in Cell Models Expressing Expanded CGG Repeats - Derbis, Magdalena; Konieczny, Patryk; Walczak, Agnieszka; Sekrecki, Michal; Sobczak, Krzysztof (Frontiers in Genetics, 2018)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset neurodegenerative disorder caused by expanded CGG (CGGexp) trinucleotides in the 5’UTR of the FMR1 gene encoding fragile X mental retardation protein (FMRP). The patients, with the number of the repeats ranging from 55 to 200, show specific manifestation of clinical symptoms that include intention tremor, gait ataxia, cognitive deficits and brain atrophy. Accumulation of toxic polyglycine (FMRpolyG), a by-product of the CGGexp repeat-associated non-ATG (RAN) translation, is considered to be one of the main factors triggering neurodegenerative processes in FXTAS patients. Nevertheless, the nature of the FMRpolyG-induced cell damage, especially in the context of its soluble and inclusion-associated forms, is still elusive. Targeting either biosynthesis, cellular stability or aggregation capacity of toxic FMRpolyG could be considered as a potential therapeutic strategy for FXTAS. Therefore, we tested a variety of quantitative methods based on forced expression of genetic constructs carrying CGGexp repeats in the context of the FMR1 5’UTR fused to GFP, mCherry or Firefly luciferase gene in or out of frame to the polyglycine encoding sequence. We show that FMRpolyG translation either from native or an AUG-induced start codon as well as the translation yield of the FMRP open reading frame equivalent located downstream of the CGGexp element can be effectively estimated using fluorescence microscopy, flow cytometry or luciferase assay. We also quantitatively estimated soluble fraction and insoluble form of FMRpolyG aggregated in foci using an electrophoretic separation of cell lysates and fluorescence microscopy, respectively. Importantly, we show that dependent on a fusion tag, FMRpolyG has a different potential for aggregate formation. Our established protocols enable sensitive tracking of FMRP and FMRpolyG quantitative and qualitative changes after treatment with potential therapeutic agents for FXTAS. Furthermore, they can be modified for application to other RAN translation- and aggregation-related diseases.